Phenological studies of two varieties of anthuriums, in the piedmont plains in nursery conditions for first and seventh semester students of Degree in Agricultural Production – Unillanos (Revista Sistemas de Producción Agroecológicos, 2012)
Given that the piedmont plains has the humid tropical conditions ideal for growing anthuriums establishment because it presents the best climatic variables for growth. This work was done in the village of Barcelona, 9 km from the urban south east of the town of Villavicencio specifically the Research Institute of the Colombian Orinoco (IIOC) of the Universidad de los Llanos located at an altitude of 400 m.s.n.m. with an average temperature of 27.5°C and average annual rainfall of 2891 mm. Considered as objective to know what aspects of phenological development and growth of anthuriums to provide these knowledge and skills to strengthen the agricultural acreage and generate production alternatives. There were two plots of 1.10 m in width and length 10 m to 140 plants, divided into 70 plants with red flowers and 70 white flowers, were randomly selected 20 plants flowered red and 20 white-flowered plants, which were numbered each. After this plot established phenological data were taken every 15 days in which data were taken as plant height, leaf number, and number of flowers. For the analysis of results used the Student t test. There were lectures and field trips to gain a better understanding. Once the experimental phase and analyzed the data we proceeded to develop the teaching phase of the research for this population was taken as the first and seventh semester students of Degree in Agricultural Production, Universidad de los Llanos. Were surveyed freshmen and seventh. The information obtained is released through information leaflets, producers and students of degree in agricultural production. The evaluation phenological development and growth of anthurium in accordance with the methodology used to determine allowed the establishment, management and production variables. The higher production of leaves and flowers during the phenological evaluation is presented in Variety anthurium album (white plants) between 1 and 2 flowers forever. Unlike the production of anthurium Variety rubrum (red plants) always maintained for 1 and often 2 to a lesser extent. However, these 2 varieties can be grown without any problem. During the time the two varieties evaluated produced flowers. However, the range Album won best response to the conditions of the Llanos Foothills. According to surveys applied to first semester students, mostly unaware of the advantages in the management and operation of anthurium cultivation, and production alternative may be in the Department of Meta.
Keywords: tropical flower; anthurium; album variety; rubrum variety; humid tropics